Investigating the effects of cognitive linguistic approach in developing EFL learners' pragmatic proficiency. (April 2020) - Takimoto, Masahiro
Abstract: The present study compared the effects of a cognitive linguistic approach, as against a non-cognitive linguistic approach, on the development of Japanese EFL learners' pragmatic proficiency concerning degrees of politeness attached to English requests. The cognitive linguistic approach applied the politeness is distance metaphor to teach different degrees of politeness. It involved a spatial concept projection through which participants understood degrees of politeness in terms of the spatially visualized concepts of near-far and high-low in an illustration. In contrast, the non-cognitive linguistic approach involved rote learning of target English biclausal mitigated requests in a list. The results demonstrated that the cognitive linguistic approach group outperformed the non-cognitive linguistic approach and control groups in a discourse completion test and an acceptability judgment test. They further suggested that the spatial concept-oriented approach using metaphors for awareness-raising is an effective mnemonic device for developing Japanese EFL learners' pragmatic proficiency, as it helps the participants facilitate deep processing of form-meaning-context connections and ensures their long-term retention. Highlights: The cognitive linguistic approach applied the politeness is distance metaphor to teach different degrees of politeness. The cognitive linguistic approach led learners to understand the degrees of politeness in terms of the spatial concepts. The politeness is distance metaphor involved proximal-distal metaphors such as near-far and high-low metaphors. The spatial concept-oriented approach is an effective mnemonic device in developing learners' pragmatic proficiency. The metaphorical mappings helped learners to facilitate deep processing of form-meaning-context connections.